Detection of micellar structures in oil-water-surfactant systems with a photoacoustic method - POGORZELSKI, S. J.; SZURKOWSKI, J.; ŚLIWIŃSKI, A. (Archives of Acoustics, 1999)
Model studies were performed with a layered system consisting of thin olive oil layers (25-250 μm in thickness) spread over the water surface using a photoacoustic method. Significant variations in the signal phase and amplitude found out at the interfaces (air/oil and oil/water) as well as at a depth of 9-13 μm beneath the oil surface point to the formation of organized clathrate molecular structures under the film-covered surfaces and micellar structures of surfactants if present in a bulk oil phase at an appropriate concentration (above CMC) and temperature (Krafft point). Such organized structures have different thermodynamic properties (like specific heat or thermal diffusivity, discussed in terms of classical thermodynamics of thin surface layers) that is supposed to affect the photoacoustic effect used for depth profiling.